2012
DOI: 10.1021/jp3006734
|View full text |Cite
|
Sign up to set email alerts
|

O2 Diffusion in Amorphous SiO2 Nanoparticles Probed by Outgassing

Abstract: An experimental study of the O 2 diffusion process in nanoparticles of amorphous SiO 2 in the temperature range from 98 to 157 °C was carried out by Raman and photoluminescence techniques. We studied O 2 diffusion in high purity silica nanoparticles with a mean diameter of 14, 20, and 40 nm detecting the outgassing of molecules trapped during the manufacturing. The kinetics of diffusion is well described for all the investigated nanoparticles by the Fick's equation proving its applicability to nanoscale system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 38 publications
(78 reference statements)
3
26
0
Order By: Relevance
“…By comparison with a previous Raman study [14], we can evaluate the concentration of O to be molecules/cm with a 50% uncertainty. This value agrees with the results on solubility for silica matrix extrapolated from data obtained in [10] at a much higher temperature, and on diffusivity at low temperature verified by works on silica nanoparticles [23]. Moreover, our experiments confirm that, at room temperature, the interstitial oxygen molecules are trapped Table II. (c) Spectral decomposition of the difference of RIA between the F2D3-O2 and F2D3 at 1 MGy.…”
Section: Discussionsupporting
confidence: 90%
“…By comparison with a previous Raman study [14], we can evaluate the concentration of O to be molecules/cm with a 50% uncertainty. This value agrees with the results on solubility for silica matrix extrapolated from data obtained in [10] at a much higher temperature, and on diffusivity at low temperature verified by works on silica nanoparticles [23]. Moreover, our experiments confirm that, at room temperature, the interstitial oxygen molecules are trapped Table II. (c) Spectral decomposition of the difference of RIA between the F2D3-O2 and F2D3 at 1 MGy.…”
Section: Discussionsupporting
confidence: 90%
“…To do this, we had to take into account the natural outgassing of the interstitial O 2 molecules in our sample [34]. With the aim to overcome this problem, we have loaded simultaneously with O 2 many samples of AEOX50 (the reader will verify in the following that the material is the one with the higher oxygen The main difference we can see is in the PL intensity at 1538 cm -1 and it is due to the difference between the O 2 concentration in the two samples.…”
Section: Resultsmentioning
confidence: 99%
“…Offering large accessibility to atomic and molecular species of the ambient atmosphere, the microscopic structure of these sites at the surface is also influenced by the environment [7]. Molecular oxygen, O 2 , plays a crucial role since it is active in several reactions and it can diffuse through the nanostructured silica [8,9]. Previous studies have demonstrated the formation of oxygen related defects by controlled thermochemical reactions.…”
Section: Introductionmentioning
confidence: 99%